275 Effects of Reduced Metabolizable Energy by Reducing fat Supplementation on Growth Performance and Intestinal Health of Nursery Pigs. (21st September 2022) - Baker, Jonathan; Duarte, Marcos Elias E; Kim, Sung Woo
Abstract: This study aimed to investigate the effects of reducing metabolizable energy (ME) by reducing fat supplementation on growth performance and intestinal health of nursery pigs. Nursery pigs (n = 120; 7.3 ± 0.6 kg BW) were allotted in a randomized complete block design with sex and initial BW as blocks. Pigs were assigned to 5 dietary treatments with decreasing ME levels (3, 400, 3, 375, 3, 350, 3, 325, and 3, 300 kcal/kg ME). ME content was gradually reduced by reducing fat supplementation (2%). Pigs were fed for 35 d in 2 phases (P1: 14 d and P2: 21 d). Titanium dioxide was added (0.4%) to P2 diets as an indigestible external marker to measure apparent ileal digestibility (AID) of nutrients. At d 35, a pig with median BW of each pen in 2 treatments (3, 400 and 3, 300 kcal/kg) was euthanized for sampling jejunal mucosa to analyze oxidative stress and immune status. Jejunal digesta was collected to measure viscosity. Ileal digesta was collected to analyze AID of nutrients. Data were analyzed using SAS. Reducing ME level by 3% (100 kcal/kg) had no effect on growth performance. The 3, 300 kcal/kg diet reduced (P < 0.05) AID of DM (59.5 to 47.3%), GE (59.1 to 43.0%), CP (63.4 to 44.6%), and EE (67.7 to 55.2%), increased (P < 0.05) digesta viscosity (1.7 to 2.2 cP) and VH:CD (1.64 to 1.80), and decreased (P < 0.05) VH (467 to 433 µm) when compared with 3, 400 kcal/kg diet. Additionally, the 3, 300 kcal/kg diet increased (P < 0.05) the concentration of protein carbonyl (0.18 to 0.40 nmol/mg) in the jejunal mucosa. In conclusion, reducing ME by reducing fat supplementation by 2% increased the viscosity of jejunal digesta and protein carbonyl in the jejunal mucosa, resulting in decreased villus height and nutrient digestibility, without affecting growth performance.